Low-Dose Intratympanic Gentamicin for Unilateral Ménière‘s Disease: Accuracy of Early Vestibulo-Ocular Reflex Gain Reduction in Predicting Long-Term Clinical Outcome - Wegmann-Vicuña, Ricardo; Manrique-Huarte, Raquel; Calavia-Gil, Diego; Martín-Sanz, Eduardo; Marques, Pedro; Perez-Fernandez, Nicolas (Frontiers in Neurology, 2022)
Background: The number of intratympanic gentamicin (ITG) injections needed to achieve vertigo control in patients with intractable Ménière’s disease (MD) may vary from a single dose to several instillations. Changes in different vestibular tests’ results have been used to define an endpoint of treatment, including the decrease of the vestibulo-ocular reflex gain elicited by the head-impulse test. Objective: To assess the accuracy of the vestibulo-ocular reflex gain reduction after horizontal canal stimulation, as measured with the video head-impulse test (vHIT) one month after the first intratympanic injection, in predicting the need of one or more instillations to control vertigo spells in the long term. Methods: The vestibulo-ocular reflex (VOR) gain reduction was calculated in 47 patients submitted to (ITG) therapy one month after the first instillation. Results: Single intratympanic treatment with gentamicin has a 59.6% efficacy in vertigo control in the long term. Hearing change in the immediate period after treatment (1 month) is not significant to pre-treatment result and is similar for patients who needed multiple doses due to recurrence. Chronic disequilibrium and the need of vestibular rehabilitation was less frequent in patients with a good control of vertigo with just one single injection of gentamicin. A fair accuracy was obtained for the VOR gain reduction of the horizontal canal (area under the curve=0.729 in the Receiver Operating Characteristic analysis) in predicting the need of one or more ITG. Conclusions: Single intratympanic treatment with gentamicin is an effective treatment for patients with MD. That modality of treatment has very limited damaging effect in hearing. The degree of vestibular deficit induced by the treatment is significant as measured by the reduction in the gain of the VOR but not useful for prognostic purposes.